2016
DOI: 10.1103/physreve.93.032108
|View full text |Cite
|
Sign up to set email alerts
|

Lossy chaotic electromagnetic reverberation chambers: Universal statistical behavior of the vectorial field

Abstract: The effective Hamiltonian formalism is extended to vectorial electromagnetic waves in order to describe statistical properties of the field in reverberation chambers. The latter are commonly used in electromagnetic compatibility tests. As a first step, the distribution of wave intensities in chaotic systems with varying opening in the weak coupling limit for scalar quantum waves is derived by means of random matrix theory. In this limit the only parameters are the modal overlap and the number of open channels.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…by validating the setup parameters such as detector linearity (by varying the input power), but no differences were observed. A similar issue has been addressed in [59], also referring to [60], as well as in [61]. Changing the antennas indeed had an effect and is discussed in the next section.…”
Section: Q-factor Dependencymentioning
confidence: 53%
See 1 more Smart Citation
“…by validating the setup parameters such as detector linearity (by varying the input power), but no differences were observed. A similar issue has been addressed in [59], also referring to [60], as well as in [61]. Changing the antennas indeed had an effect and is discussed in the next section.…”
Section: Q-factor Dependencymentioning
confidence: 53%
“…The work presented in [60] and more recent [59] address the issue of obtaining a different distribution than Rayleigh, depending on the selection of antennas. Apart from that, a relation between the antenna aperture and statistics of the recorded field is expected on the basis of a deviation from the theoretical assumptions of a infinitesimal (point) antenna as assumed in the PWIR theory.…”
Section: Antenna Dependencymentioning
confidence: 99%
“…The corresponding working volume is about 19 m 3 . In our previous studies based on simulations and measurements we showed that the field uniformity can be improved in this cavity by adding metallic hemispheres on its metallic walls [1], [2], [4], [5]. The basic idea of this geometrical modification is, in the first instance, to avoid the presence of flat parallel metallic surfaces as they permit regular resonant modes to establish as, for instance, those associated with the multiple reflections between two facing flat parallel surfaces.…”
Section: B Modification Of a Conventional Reverberation Chambermentioning
confidence: 99%
“…It has been demonstrated [5], [8] that for a chaotic system in the weak coupling regime, for weak or moderate modal overlap, the distribution of the resonance widths follows a χ 2 law with M degrees of freedom, with M calculated as:…”
Section: B Distribution Of the Resonance Widthsmentioning
confidence: 99%
See 1 more Smart Citation